Analisis Kinerja Simpang Tiga Tak Bersinyal (Studi Kasus Jl. Bondowoso – Jl. Jombang, Kota Malang) - Irene Marlina Gollu; Pamela Dinar Rahma; M. Sadillah (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2025)
Traffic congestion problems in urban areas often stem from the inefficiency of unsignalized intersections, as observed at the three-way intersection of Jalan Bondowoso and Jalan Jombang in Malang City. This study aims to evaluate the operational conditions of this type 322 intersection, located in a commercial area, using the 2023 Indonesian Road Capacity Guidelines (PKJI) and to formulate effective mitigation solutions. Based on field surveys, the highest peak traffic volume was recorded on Tuesday from 4:00 p.m. to 5:00 p.m. Western Indonesian Time, reaching 5,844 vehicles/hour. Performance analysis shows that the current condition of the intersection is approaching a critical limit, with a capacity (C) of 3,348 vehicles/hour and a degree of saturation (Dj) of 0.77. These parameters place the intersection at Level of Service (LOS) D, characterized by unstable traffic flow and decreasing speeds. Furthermore, a five-year performance projection estimates a sharp degradation, with the degree of saturation surging to 1.76, resulting in Level of Service F, or total traffic congestion. To prevent this decline, a series of alternative solutions are proposed, including widening Jalan Bondowoso to 8.5 meters and Jalan Jombang to 7 meters, adding a 0.5-meter median to the major road, and implementing traffic management measures such as prohibiting right turns and parking/stopping at all intersection arms. Simulation results demonstrate that these solutions can significantly improve performance, reducing the degree of saturation to 0.69 and upgrading the Level of Service to C. This indicates that traffic flow can be stabilized through appropriate physical modifications and regulations.